Psychological capital and psychological career mobility among Finnish business school graduates - Järlström, Maria; Brandt, Tiina (Sam Houston State University, 2017)
This article studies the relationship between psychological capital and psychological career mobility through a sample of 624 Finnish business-school graduates. The findings indicate that psychological capital and its dimensions are positively related to internal and external psychological career mobility. A typology of four careerist types is defined from psychological capital and internal and external psychological career mobility dimensions through cluster analysis. The Finnish respondents could be divided into four distinct groups: Ambitious Careerist, Change-Oriented Careerist, Insecure Anti-Careerist, and Stable Career-Developer. The Ambitious Careerist demonstrated far higher levels of psychological capital than any other careerist type. At the end of the article, new insights related to psychological elements of career research are discussed.
Keywords: psychological capital; psychological career mobility; boundaryless careers; fi=Johtaminen ja organisaatiot|en=Management and Organization|